2022
DOI: 10.15419/bmrat.v9i2.728
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia hirta as a gold mine of high-value phytochemicals: A comprehensive review of its pharmacological activities and possible role against SARS-CoV-2

Abstract: Euphorbia hirta is a common medicinal plant in folk and traditional medicine systems. This plant has shown promising effects against several human ailments and infectious diseases. Therefore, it is important to summarize the medicinal activities and value of Euphorbia hirta. The main intent of this literature review was to summarize the phytochemical content and pharmacological applications of Euphorbia hirta. The literature review about the pharmacology and phytochemistry of Euphorbia hirta was collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As literature indicated, the conclusive remarks could be confirmed the following reasoning: (a) major content of T. khasianum was rosmarinic acid (i.e., o -diOH bearing ES) and (b) predominant compositions of E. hirta were euphrobianin, quercetin, quercetin 3- O -alpha-rhamnoside, isoquercitrin, and rutin (i.e., o -diOH bearing ESs). Due to abundance in biocompatible ES species, these two herbal extracts could be considered to be top-priority selection for anti-COVID-19 drugs [ 30 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As literature indicated, the conclusive remarks could be confirmed the following reasoning: (a) major content of T. khasianum was rosmarinic acid (i.e., o -diOH bearing ES) and (b) predominant compositions of E. hirta were euphrobianin, quercetin, quercetin 3- O -alpha-rhamnoside, isoquercitrin, and rutin (i.e., o -diOH bearing ESs). Due to abundance in biocompatible ES species, these two herbal extracts could be considered to be top-priority selection for anti-COVID-19 drugs [ 30 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Euphorbia hirta aerial parts (Fēi Yánɡ Cǎo), the dried aerial parts extracts of E. hirta showed the antioxidant property using DPPH and FRAP assays, and its anti-diabetic activity were evaluated by glucose uptake assay [50] . E. hirta widely distributed in Asia, it has been found for many biological activities which including antioxidant, anti-bacterial, anti-venom, antimalarial and antiviral (e.g., HIV, DANV, HSV activities) [ 41 , 42 , 51 ]. The literatures have been reported for E. hirta anti-COVID-19 activity using two different targets of SARS-CoV-2, namely Main protease (Mpro; PDB ID: 6M2N ) and RNA-dependent RNA polymerase (RdRp; PDB ID: 7BW4 ) recently.…”
Section: Resultsmentioning
confidence: 99%
“…They are very 2 of 12 diverse in their morphological and ecological characteristics, and many of them have been used for various purposes since ancient times owing to their excellent pharmacological properties [10][11][12]. For example, it has been reported that Euphorbia hirta, also known as garden spurge, shows antidiarrhoeic and anti-inflammatory activities and can also be used to treat digestive problems, respiratory system disorders, injuries, and skin cellular tissue disorders [13][14][15][16][17]. There are also several reports on the use of various plants of the Euphorbia genus for medicinal purposes [10].…”
Section: Introductionmentioning
confidence: 99%